The Distributional Incidence of Residential Water and Electricity Subsidies - Komives, Kristin (World Bank, Washington, DC, 2012)
Subsidies to residential utility customers are popular among policymakers, utility managers, and utility customers alike, but they are nonetheless the subject of much controversy. Utility subsidies are seen as a way to help make utility service affordable for poor households and as an alternative mechanism for income redistribution. These arguments in favor of subsidies are countered by serious concerns about their adverse effects on consumer behavior, utility operations, and the financial health of utilities. Both the affordability and redistributive arguments for subsidies are based on the presumption that poor households benefit disproportionately from water and electricity subsidies, that they are well-targeted to the poor. The authors test this assumption by examining the extent to which the poor benefit from consumption and connection subsidies for water and electricity services. Their analysis of a wide range of subsidy models from around the developing world shows that the most common form of utility subsidy-quantity-based subsidies delivered through the tariff structure-are highly regressive. Geographically targeted or means-tested subsidies do better, and in many cases have a progressive incidence, but large numbers of poor households remain excluded. Low levels of coverage and metering severely limit the effectiveness of consumption subsidy schemes to reach the poor. Simulations suggest that connection subsidies are an attractive alternative for low coverage areas, but only if utilities have the means and motivation to extend network access to poor households and only if those households choose to connect.